2020
DOI: 10.1002/jmri.27348
|View full text |Cite
|
Sign up to set email alerts
|

Shoulder MR Arthrography: Comparative Evaluation of Three Different Contrast Injection Techniques Using an Anterior Approach

Abstract: BackgroundMR arthrography (MRA) is commonly used in the assessment of shoulder internal derangements. Correct intra‐articular contrast injection is required for this modality. Anterior injections under fluoroscopic, ultrasound‐guidance, or without image‐guidance have been described in the literature. However, no simultaneous comparison has been performed between the three techniques.PurposeTo compare the accuracy and performance of fluoroscopy (FL)‐guided, ultrasound (US)‐guided and non‐image‐guided intra‐arti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…In this sequential, prospective trial, we presented a new anterior landmark-based approach without the use of ultrasound, and found it was more accurate than the posterior approach. Moreover, the new anterior approach is nearly as accurate as other published ultrasound-guided approaches [1, 5, 9, 11, 13]. Consequently, we recommend using the new anterior approach in practice as it will save time and the cost associated with ultrasound.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…In this sequential, prospective trial, we presented a new anterior landmark-based approach without the use of ultrasound, and found it was more accurate than the posterior approach. Moreover, the new anterior approach is nearly as accurate as other published ultrasound-guided approaches [1, 5, 9, 11, 13]. Consequently, we recommend using the new anterior approach in practice as it will save time and the cost associated with ultrasound.…”
Section: Discussionmentioning
confidence: 98%
“…In this prospective study, we compared two landmark-based approaches: the posterior approach and a new anterior injection approach. The new anterior approach, without the use of ultrasound, is nearly as accurate as other published ultrasound-guided approaches [1, 5, 9, 11, 13]. Therefore, we recommend using the new anterior approach for intraarticular glenohumeral injections.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Direct contrast injection can be performed under fluoroscopic guidance and ultrasound guidance or by palpation. Both fluoroscopic and ultrasound guidance have high accuracy (up to 100%) and are preferred over non-image-guided injection [ 20 ]. The accuracy of fluoroscopic versus ultrasound-guided contrast injection is comparable, although ultrasound has the advantage of lack of radiation and may be better tolerated.…”
Section: Glenohumeral Jointmentioning
confidence: 99%
“…The accuracy of fluoroscopic versus ultrasound-guided contrast injection is comparable, although ultrasound has the advantage of lack of radiation and may be better tolerated. Two studies comparing ultrasound versus fluoroscopic-guided contrast injection showed significantly shorter procedure times and lower reported pain for ultrasound-guided procedures [ 20 , 21 ].…”
Section: Glenohumeral Jointmentioning
confidence: 99%